Investing in multi-stakeholder dialogue to address natural resource competition and conflict - Ratner, Blake D.; Burnley, Clementine; Mugisha, Samuel; Madzudzo, Elias; Oeur, Il (Informa UK Limited, 2018)
How can multi-stakeholder dialogue help assess and address the roots of environmental resource competition and conflict? This article summarises the outcomes and lessons from action research in large lake systems in Uganda, Zambia, and Cambodia. Dialogues linking community groups, NGOs and government agencies have reduced local conflict, produced agreements with private investors, and influenced government priorities in ways that respond to the needs of marginalised fishing communities. The article details policy guidance in four areas: building stakeholder commitment, understanding the institutional and governance context, involving local groups in the policy reform process, and embracing adaptability in programme implementation.